1984
DOI: 10.1093/schbul/10.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Schizoaffective Disorders

Abstract: Studies that compare the treatment response of patients diagnosed as primary affective disorder or schizoaffective disorder are reviewed. Although relatively few controlled or uncontrolled studies of the chemotherapy of schizoaffective disorders have been conducted, available evidence suggests that: (1) lithium carbonate is effective in the initial treatment of both schizoaffective mania and mania; (2) antidepressants alone, neuroleptics alone, or their combination can be effective in the initial treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 58 publications
2
9
0
1
Order By: Relevance
“…The finding that LiCl feeding upregulated baseline values of k* for AA in central auditory and visual areas of rat brain (see Results), which agrees with our previous observations (Basselin et al, 2005(Basselin et al, , 2003b, may be related to these clinical effects and to lithium's ability to reduce visual and auditory hallucinations in bipolar disorder patients (Goodnick and Meltzer, 1984;Potash et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…The finding that LiCl feeding upregulated baseline values of k* for AA in central auditory and visual areas of rat brain (see Results), which agrees with our previous observations (Basselin et al, 2005(Basselin et al, , 2003b, may be related to these clinical effects and to lithium's ability to reduce visual and auditory hallucinations in bipolar disorder patients (Goodnick and Meltzer, 1984;Potash et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Delva and Letemendia [19] reviewed lithium studies with regard to SAD, finding that the majority of studies found evidence for prophylactic effectiveness. The same conclusion was drawn by Goodnick and Meltzer [29] from 10 prophylaxis studies using lithium. Taylor [68], in his comprehensive overview, points out that most patients will benefit from lithium in the long-term treatment; however, Levinson and coworkers [41] came to the opposite conclusion.…”
Section: Introductionsupporting
confidence: 79%
“…In clinical practice, treatment decisions for SAD patients are often made by an analogy to schizophrenia or affective disorders. However, despite the bias described above, patients suffering from schizoaffective disorder often perform differently in longterm treatment studies when compared with patients with other diagnoses [29]. Thus, in long-term treatment studies including different disorders, it seems justified from empirical evidence to concentrate on the SAD cases.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The elevations also may be related to the ability of toxic doses of lithium to cause auditory or visual hallucinations (Hambrecht and Kaumeier, 1993) or photophobia (Pridmore et al, 1996). On the other hand, lithium's blocking of the k* increments in response to DOI, a recognized hallucinogen (Sadzot et al, 1989), in visual and auditory areas and the substantia nigra and locus coeruleus, may relate to its ability to reduce hallucinations in bipolar disorder (Goodnick and Meltzer, 1984;Potash et al, 2001;Rosenthal et al, 1979).…”
Section: Discussionmentioning
confidence: 99%